Sixteen novel hemophilia A causative mutations in the first Argentinian series of severe molecular defects - Rossetti, Liliana Carmen (2007)
Hemophilia A (HA) is caused by heterogeneous mutations in the factor VIII gene (F8). This paper reports 16 novel small F8-mutations and rearrangements in a series of 80 Argentinian families with severe-HA. Using an updated scheme for F8-analysis, we found 37 F8-inversions (46%), 10 large deletions (13%), 13 small ins/del (16%), 7 nonsense (9%) and 8 missense mutations (10%), including 4 new ones (p.T233K, p.W1942R, p.L2297P and p.L2301S). The potential changes leading to severe-HA of these latter mutations were suggested by bioinformatics. The F8-mutation was characterised in 76 families (95%). They received genetic counselling and precise information about treatment design. ©2007 Ferrata Storti Foundation.